An evaluation of early and delayed laparoscopic cholecystectomy for acute cholecystitis - Imbisat, M. Zaid; Rizvi, S. A. A.; Ali, Imad (International Surgery Journal, 2019)
Background: Acute cholecystitis is one of the hepatopancreatobiliary emergencies. With more and more experience in the laparoscopic cholecystectomy studies are being carried out evaluating the effectiveness and feasibility of early laparoscopic cholecystectomy in acute cholecystitis. Methods: Fifty patients presenting with acute cholecystitis were included in this study and randomized using chit in the box method into two groups- early group and delayed group. Results: Mean duration of surgery in the early group is 42.28±5.99 mins and in the delayed group is 39.12±5.55 mins (p=0.06). Gallbladder perforation was reported in 4 patients (16%) in early group and in 2 patients (8%) in delayed group (p=0.67). Gall stone spillage was reported in 3 patients (12%) in early group and in 2 patients (8%) in delayed group (p=1.00). At 6th hr mean VAS (visual analogue scale) score in the early group was 4.0±0.41 and in the delayed group it was 3.6±0.58 (p=0.01). At 12th hr mean VAS score in the early group was 3.4±0.51 and in the delayed group it was 3.3±0.48 (p=0.39). Mean duration of postoperative stay was 2.24±0.60 days in early group and in the delayed group it was 2.08±0.57 days (p=0.34). Conclusions: It has been found that early laparoscopic cholecystectomy is safe and feasible in the setting of acute cholecystitis with added advantage of shorter total hospital stay.